African ecology benchmarks and historical perspectives - Spinage, Clive Alfred (Springer Geography, 2012)
In view of the rapidly changing ecology of Africa ,this work provides benchmarks for some of the major, and more neglected, aspects, with an accent on historical data to enable habitats to be seen in relation to their previous state, forming a background reference work to understanding how the ecology of Africa has been shaped by its past. Reviewing historical data wherever possible it adopts an holistic view treating man as well as animals, with accent on diseases both human and animal which have been a potent force in shaping Africa's ecology, a role neglected in ecological studies.